Advanced Simulation and Modeling Technologies of Metallurgical Processes—1st Edition - Haifeng Li; Junqi Li (Metals)
Due to rapid developments in computer technologies over the last two decades, computer-based process modeling has become an important tool for the improvement of existing process technologies and the development of innovative ones [...]